Variabilidad espacial y temporal de la precipitación lluviosa en Paraguay - Báez, Julián (1994)
The spatial and temporal rainfall distributions over Paraguay are analyzed. Twenty one stations distributed over the country, most of them with records longer than 30 years, are used. For each one, the average monthly and yearly distributions are pre-sented. Rainfall maps of the monthly and annual averages are also presented. The main conclusions are: 1) The minimum rainfall values occur in winter, in July and August, over all the territory. A secondary minimum is observed in the middle of the summer (February or March) in the Oriental region. 2) The largest rainfall amounts occur during the summer semester, being October and November the rainiest months, mainly in the Oriental region. A secondary maximum occur in April. 3) In the Occidental region, the maximum values are observed in the middle of the summer, from December to February 4). The eastern and southeastern parts of the country are the rainiest regions. Low values are observed in the central and southwestern parts of the Oriental region. The Occidental region, mainly in its north-western border, is the driest. 5) Rainfall values larger than the average are related with ENSO events, mainly with the strong events. During "La Niña" of 1976 and 1988, all stations show rainfall values below the average.